The new universal definition of myocardial infarction criteria improve electrocardiographic diagnosis of acute coronary syndrome - Fleischmann, Kirsten E.; Zègre-Hemsey, Jessica; Drew, Barbara J. (Journal of electrocardiology, 2011)
To assess whether revised electrocardiographic (ECG) criteria improve emergency department identification of patients with acute myocardial infarction (MI) or unstable angina (UA) and predict outcome, we studied 120 patients with a nondiagnostic initial ECG by prior criteria. Electrocardiograms were read in a blinded fashion months apart with standard and then revised criteria, and analyzed by χ 2 and logistic regression analysis. In 12 subjects (10%), the initial ECG was now interpreted as diagnostic of ischemia. Eleven (92%) had an MI, 1 had UA (8%), and none had a noncardiac diagnosis. Ischemic ECG changes were strongly associated with MI or UA ( P = .003). At 1-year follow-up, ECG changes diagnostic of ischemia were associated with a trend toward higher mortality (25% vs 7%, P = .07), but after adjustment for clinical factors, ECG changes were not an independent predictor of 1-year mortality. Revision of the ECG criteria for ischemia was associated with enhanced diagnostic performance and identified a subset of patients at higher risk.